Efektivitas Pijat Oksitosin oleh Suami terhadap Kecukupan ASI Berdasarkan Frekuensi Buang Air Besar dan Lama Tidur Bayi - Kanang, Bau; Ibrahim, Nur Susan Iriyanti; Masse, Ade Fadly (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Perceived breast milk insufficiency during early postpartum is a major contributor to the failure of exclusive breastfeeding. Oxytocin massage is a non-pharmacological intervention that may enhance milk ejection reflex, particularly with spousal involvement. Objective: This study aimed to analyze changes in breast milk adequacy indicators following husband-performed oxytocin massage based on infant defecation frequency and sleep duration. Methods: A quasi-experimental one group pretest–posttest design was conducted among 29 postpartum mothers selected purposively in Bajeng and Pabbentengan Primary Health Centers, Gowa Regency. Husbands performed oxytocin massage for three consecutive postpartum days. Breast milk adequacy was assessed using infant defecation frequency and sleep duration. Data were analyzed using the Wilcoxon test (p < 0.05). Results: Infant defecation frequency increased significantly from pretest to day three posttest (p < 0.001). Infant sleep duration showed no significant difference on day one (p = 0.141), but significant increases were observed on day two (p = 0.032) and day three (p = 0.007). Conclusion: Husband-performed oxytocin massage was associated with improvements in breast milk adequacy indicators during early postpartum. However, due to the absence of a control group, causal inference should be interpreted cautiously.